THE IMPACT OF SOLVENCY AND WORKING CAPITAL ON PROFITABILITY - Yenni, Yenni; Arifin, Arifin; Gunawan, Eddy; Pakpahan, Leonard; Siregar, Halasan (AGUSPATI Research Institute, 2021)
Every business requires working capital for its survival. A solvent company has assets that exceed its liabilities sufficiently to reinvest in its growth. Solvency refers to company's ability to fulfil its obligations. Assessment of a company's ability to pay it obligations such as to make interest and principal payments generally include analysis of the components of its financial structure. The degree of solvency in a business is measured by the relationship between the assets, liabilities and equity of a business at a given point in time. The company should determine the appropriate solvency levels in increasing profitability. The purpose of this research is to know whether solvency and working capital have an impact on profitability at CV Masindo Electric Medan. The research design used in this research is a descriptive research design with conducting financial statement analysis. Research methods used are descriptive statistic analysis with financial ratio analysis, coefficient correlation, coefficient of determination, linear regression analysis, t test and F test.This research concludes that solvency and working capital have impact on profitability at CV Masindo Electric Medan. Based on T-test, the value of Tcount is higher than Ttable. Therefore, the solvency and working capital have a significant impact on profitability at CV Masindo Electric Medan partially. Based on the F test, the value of Fcount is higher than Ftable. Therefore, the solvency and working capital have a significant impact on profitability at CV Masindo Electric Medan simultaneously. The profitability can be explained by working capital and solvency in 99.8%, while the remaining in 0.2% is explained by other factors. Based on the working capital analysis, there is decrease in working capital in the year 2012-2016. It shows that the company doesn't conduct working capital management appropriately. Based on solvency analysis, there is increasing insolvency in the year 2012-2016. The company has limitations from internal fund from profit and capital from the owner. Therefore, the company finds a way to conducting business with external funds such as from account payable and bank loan. Based on profitability analysis, it can be known that there is decreasing of profitability in year 2012-2016. The company cannot increase the sales price to a high level because there is low-profit margin. Keywords: Solvency, Working Capital and Profitability